Efektivitas Media Tumbuh Maggot (Hermetia illucens) Berbasis Limbah Pertanian Sebagai Bahan Pakan Sumber Protein - Nur'aini; Ulina Hutasuhut (Jurnal Ilmu dan Industri Peternakan, 2024)
This study aims to determine the best growth media of maggot (Hermetia Illucens) including media conditions, temperature and pH of media, media shrinkage through the use of agricultural waste. This study used a Non-Factorial Complete Randomized Design (RAL) with 5 treatments and 3 repeats. The treatment given in this study is: P0A = bran 100%; P0b = 100% vegetable and fruit waste; P1 = bran 75 % + vegetable and fruit waste 25 %; P2 = bran 50 % + vegetable and fruit waste 50 %; P3 = bran 25% + vegetable and fruit waste 75%. The results showed that maggot growing media from mixing 50% bran with 50% vegetable and fruit waste (P2) is the best growing media and suitable for maggots both in terms of media conditions, temperature and media pH, so that the use of growing media as feed for maggots is more optimal and effective which is shown by the high media shrinkage value. The condition of the growing media from P2 is brown, quite smooth, moist and not moldy with a pH of 5 - 6.03 and a media temperature of 23.27 - 26.73 OC with a media shrinkage of 1,540 g. It was concluded that maggot growing media with the same ratio of mixing bran agricultural waste with vegetable and fruit waste can produce high media shrinkage with conditions, temperature and pH of the growing media suitable for the needs of maggot life.